Stages in Colicin K Action, as Revealed by the Action of Trypsin - Plate, C. A. (1972)
The effects of trypsin on Escherichia coli cells that have been treated with colicins have been examined. By the use of trypsin, it has been possible to demonstrate that the action of several colicins (E1, E2, and K) proceeds through at least two stages. Stage I is a period after colicin adsorption when trypsin can restore colony-forming ability to a colicin-treated cell. Stage I is followed by a period when trypsin is unable to restore colony-forming ability (stage II). The transition between stage I and stage II follows first-order kinetics, with a rate proportional to the number of killing units of colicin adsorbed. A quantitative comparison of the effects of colicin K on colony-forming ability and on several cellular processes indicates that colicin damage to these processes occurs in the stage II period of colicin action and is not subject to reversal by the trypsin treatment that restores viability to cell in stage I. The implications of these findings for an understanding of the mode of action of colicins are discussed.